Business Development Strategies in the Tourism Industry in Langkat Regency - Samrin (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
Langkat Regency has great tourism potential, but it has not been utilized optimally. This study aims to identify and analyze effective business development strategies for the tourism industry in Langkat Regency. The research method used is a qualitative approach with data collection techniques through in-depth interviews with tourism business people, local governments, and local communities. The results of the study show that potential business development strategies include the development of unique and attractive tourism products, improving the quality of tourism infrastructure and facilities, effective tourism marketing and promotion, developing competent tourism human resources (HR), partnerships between the government, business people, and the community, and sustainable tourism development. The implication of this study is the need for synergy between various related parties to implement the business development strategies that have been identified so that the tourism industry in Langkat Regency can grow rapidly and make a significant contribution to the regional economy